Head-to-head comparison of protocol modifications for the generation of collagen-induced arthritis in a specific-pathogen free facility using DBA/1 mice. (March 2016) - Thornton, Sherry; Strait, Richard T.
Collagen-induced arthritis (CIA) is a widely used mouse model for studying inflammatory arthritis (IA). However, CIA induction protocols differ between laboratories, and direct comparison between protocol variations has not been reported. To address this issue, DBA/1 mice housed in conventional and specific-pathogen free (SPF) facilities were administered various combinations of two doses of collagen type II (CII) in complete (CFA) or incomplete Freund's adjuvant (IFA); some mice were also injected with lipopolysaccharide (LPS) and/or additional CII at specific intervals. Mice were evaluated for IA over the subsequent 2 months. Depending directly on the combination of CII, CFA, IFA, and LPS used, the incidence of IA ranged between 20%–100%, and severity extended from mild to severe even in an SPF environment. Our results demonstrate for the first time in head-to-head comparisons that specific variations in the use of CII, CFA, IFA, and LPS can induce a range of arthritic disease intensity and severity in an SPF facility. Thus, distinct experimental settings can be designed for robust assessment of factors that either exacerbate or inhibit arthritis pathogenesis. Furthermore, by achieving 100% incidence in an SPF facility, the protocols provide a practical and humane benefit by reducing the number of mice necessary for experimental assessment.